2020
DOI: 10.33549/physiolres.934169
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Gastric Norepinephrine With β-Adrenoceptors and Gastric Dysmotility in a Rat Model of Functional Dyspepsia

Abstract: Disordered motility is one of the most important pathogenic characteristics of unctional dyspepsia (FD), although the underlying mechanisms remain unclear. Since the sympathetic system is important to the regulation of gastrointestinal motility, the present study aimed to investigate the role of norepinephrine (NE) and adrenoceptors in disordered gastric motility in a rat model with FD. The effect of exogenous NE on gastric motility in control and FD rats was measured through an organ bath study. The expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Dysmotility in FD is associated with an imbalance in the ENS. 32 YKS is not effective in improving abnormal movements, indicating that its efficacy is limited in the ENS. In contrast, RKT was effective against dysmotility in FD via enhancement of ghrelin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Dysmotility in FD is associated with an imbalance in the ENS. 32 YKS is not effective in improving abnormal movements, indicating that its efficacy is limited in the ENS. In contrast, RKT was effective against dysmotility in FD via enhancement of ghrelin secretion.…”
Section: Discussionmentioning
confidence: 99%
“… 66 High norepinephrine levels may lead to gastric motility disorders. 67 This might explain why paroxetine is more likely to cause gastrointestinal side effects than citalopram.…”
Section: Discussionmentioning
confidence: 99%
“…For example, n-butanol fraction extracted from taraxacum officinale enhanced the contraction of both fundus and antrum to increase the intra-gastric pressure and lead to accelerated gastric emptying [50]. In another study, the enhanced expression of β-adrenoceptors and norepinephrine transporter in the corpus of rat with functional dyspepsia contributes to the delayed gastric emptying [51]. Our experiment found that the expression of CaSR in the myenteric plexus of gastric antrum was higher than that in the gastric corpus.…”
Section: Discussionmentioning
confidence: 99%